A second chance: Experiences and outcomes of people with dementia and their families participating in a dementia reablement program. Issue 3 (16th December 2020) - Rahja, Miia; Culph, Jennifer; Clemson, Lindy; Day, Sally; Laver, Kate
Abstract: Rationale: Evidence-based reablement programs for people with dementia and their caregivers are not routinely implemented in practice. These programs have been shown to be effective in delaying functional decline and improving caregiver wellbeing. Yet, little is known about the experiences of those participating in such programs. Aim: To describe experiences and outcomes of participating in a dementia reablement program, the Care of Persons with dementia in their Environments (COPE), in Australia. Methods: Purposeful sampling was used and semi-structured interviews were completed with people with dementia and their caregivers who received the COPE program in two different states in Australia. The interviews explored the participants' experiences with the program as well as how they are managing after program completion. Thematic analysis was used to identify themes from the interviews. A Likert scale was used to rate the value of the program. Results: Ten dyads (person with dementia and/or their caregiver) were interviewed. Participation in the program was rated (mostly) very valuable. The ongoing collaboration between the therapist and caregiver was considered empowering. The program promoted participation in everyday activities for the person with dementia and appeared to give a 'second chance' to remain in their own homes and communities. Conclusion: Participation in reablement programs (such as the COPE program) has the potential to re-engage people with dementia in meaningful roles and activities in their chosen environments. A therapeutic relationship and individualized intervention approaches tailored to the participants' needs and readiness foster positive experiences and confidence.